Interleukin-27 Early Impacts Leishmania infantum Infection in Mice and Correlates with Active Visceral Disease in Humans - Pérez-Cabezas, Begoña; Cecílio, Pedro; Robalo, Ana Luisa; Silvestre, Ricardo; Carrillo, Eugenia; Moreno, Javier; San Martín, Juan V.; Vasconcellos, Rita; Cordeiro-da-Silva, Anabela (Frontiers in Immunology, 2016)
The complexity of Leishmania–host interactions, one of the main leishmaniasis issues, is yet to be fully understood. We detected elevated IL-27 plasma levels in European patients with active visceral disease caused by Leishmania infantum, which returned to basal levels after successful treatment, suggesting this cytokine as a probable infection mediator. We further addressed this hypothesis recurring to two classical susceptible visceral leishmaniasis mouse models. BALB/c, but not C57BL/6 mice, showed increased IL-27 systemic levels after infection, which was associated with an upregulation of IL-27p28 expression by dendritic cells and higher parasite burdens. Neutralization of IL-27 in acutely infected BALB/c led to decreased parasite burdens and a transient increase in IFN-γ+ splenic T cells, while administration of IL-27 to C57BL/6 promoted a local anti-inflammatory cytokine response at the site of infection and increased parasite loads. Overall, we show that, as in humans, BALB/c IL-27 systemic levels are infection dependently upregulated and may favor parasite installation by controlling inflammation.